Pengaruh Kompetensi, Independensi, dan Motivasi Auditor Internal terhadap Efektivitas Struktur Pengendalian Internal Pada Kalla Group - Nurbayani Nurbayani; Muliana Muliana (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2019)
This research aims to analyze and prove the effect of competency, independecy and motivation intern auditor on the effectiveness structure of internal control on the group kalla. The sample of research consists of 30 respondens they are intern auditor of kalla group. The research data uses kuesioner. The analysis technique of research data uses multiple regretion analysis. The empirical results find that kompetence, can determine effectiveness of internal control, but independece and motivation can’t determine effectiveness of internal control on the group kalla